2020
DOI: 10.1111/1742-6723.13620
|View full text |Cite
|
Sign up to set email alerts
|

Intubation practices for children in emergency departments and intensive care units across Australia and New Zealand: A survey of medical staff

Abstract: Objective: Intubation of children in the emergency setting is a high-risk, low incidence event. Standardisation of clinical practice has been hampered by a lack of high-quality evidence to support one technique over another. The aim of the present study is to determine clinician preference in intubation practice of children in EDs and ICUs in Australia and New Zealand to provide baseline information to allow future targeted research focused on improving the safety and efficacy of paediatric emergency airway ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…7 A 2020 study identified significant variation in clinical practice in Australian and New Zealand EDs and ICUs, with further research recommended to determine best practice in paediatric airway management. 21 Challenges in paediatric trauma care include low exposure and associated reduced confidence which impacts proficiency to delivery of appropriate care. 7 Clinical experience alone is not sufficient to maintain skill competence and there is a need to implement strategies, such as high fidelity simulation, to support maintenance of critical skills.…”
Section: Critical Interventionsmentioning
confidence: 99%
“…7 A 2020 study identified significant variation in clinical practice in Australian and New Zealand EDs and ICUs, with further research recommended to determine best practice in paediatric airway management. 21 Challenges in paediatric trauma care include low exposure and associated reduced confidence which impacts proficiency to delivery of appropriate care. 7 Clinical experience alone is not sufficient to maintain skill competence and there is a need to implement strategies, such as high fidelity simulation, to support maintenance of critical skills.…”
Section: Critical Interventionsmentioning
confidence: 99%